The Role of ESP in Fostering EFL Students' English Competence - Muhammad Basri Dalle; Sitti Halijah; Hadijah Hadijah (Tamaddun Life, 2018)
English for Specific Purposes (ESP) has a role in developing the students’ competence if the learning programs and materials are designed and developed based on their needs. Language coverage in ESP in certain cases is different from general English. ESP programs and materials are goal-oriented, therefore it needs to be understood that English has function and role as a tool of communication in conveying thoughts and feelings to others. The well-designed and developed ESP programs and materials are expected to have a role to improve their English competence specifically. Thus, it is expected that the graduates of English language and literature will be able to master their fields and English in other science fields specifically.